Heavy metals and eggshell coloration in House Sparrow (Passer domesticus) eggshells across the Eastern United States - Suzanne Hartley; Caren Cooper; Mariah Patton; Chris Hawn; Kathryn Jewell; Aubrey Wiggins; Memuna Khan; Daniel Hanley (PLoS ONE, 2026)
House Sparrows ( Passer domesticus ) may serve as suitable species to monitor persistent environmental contaminants, like heavy metals, that pose serious health risks to humans and wildlife alike. Avian eggshells have the potential to be used as indicators of environmental contaminants since these can alter many chemical pathways, including those involved in forming and depositing avian eggshell pigmentation. Here we tested House Sparrow eggs for heavy metals and examined whether eggshell pigmentation predicted heavy metal concentrations. As part of the citizen science project, Sparrow Swap, volunteers across the United States collected 536 clutches, totaling 2,182 House Sparrow eggs. We then tested whether metal concentrations were predicted by coloration and speckling of these eggs or eggshell thickness and calcium concentration. We found that metals, including As, Se, Cd, Cu, and Pb, were present in detectable levels in House Sparrow eggs from across the country. Although eggshell characteristics were not strong predictors of metal concentrations, metal concentrations in the eggshells were higher than expected and warrant further investigation.